A Pragmatic Analysis of Gikuyu Euphemisms Used As Face-Saving Acts in The Gikuyu Political Discourse in Kiambu County, Kenya - Mwangi, Maryanne Njeri; Githiora, John Chege (International Journal of Humanity and Social Sciences, 2026)
Purpose: In Kenya today, many politicians have faced significant backlash from the public regarding their statements, often attributing their situations to being “misquoted”. For a politician, being straightforward can lead to dismissal from their elective or appointed positions or result in the loss of an elected position. As a result, politicians frequently opt for indirect communication to maintain their reputations, often using euphemisms. This study focused on politicians from the Central Region of Kenya, specifically Kiambu County, who speak Gikuyu, which is the language relevant to the research topic. The research examined the discourse of 10 politicians, comprising 5 women and 5 men. The three main objectives of the study were: (a) to analyze the Gikuyu euphemisms used by politicians in Kiambu County as face-saving strategies; (b) to explore how politicians utilize euphemisms to protect their public image; and (c) to assess the impact of these euphemisms on the electorate. Methodology: The study primarily referenced Brown and Levinson’s Politeness Theory, along with other related materials on politeness. The researcher gathered data through direct interviews at live political rallies and by observing attendees at these events. Primary data was collected from these sources, while secondary data was sourced from recorded Gikuyu political speeches available on YouTube, as well as from radio and television interviews. The gathered data were analyzed qualitatively using Brown and Levinson’s politeness theory (1978, 1987) as the framework. A purposive sampling technique was employed for the study. Findings: The findings indicated that politicians frequently use euphemisms as a method of saving face in their public discourse. Unique Contribution to Theory, Practice and Policy: This study recommends raising public awareness of political euphemisms.